Proposal for the Evaluation of Open Data Portals (2019)
The provision of portals that serve as a source of access and availability of public domain data is part of the adoption of public policies that some government entities have implemented in response to the establishment of an open, transparent, multidirectional, collaborative and focused on citizen participation government, both in monitoring and in making public decisions. However, the publication of this data must meet certain characteristics to be considered open and of quality. For this reason, studies arise that focus on the approach of methodologies and indicators that measure the quality of the portals and their data. For the aim of this paper, the search of referential sources of the last six years regarding the evaluation of data quality and open data portals in Spain, Brazil, Costa Rica, Taiwan and the European Union was carried out with the objective of gathering the necessary inputs for the approach of the methodology presented in the document.